Chicken Feather Waste Valorization Into Nutritive Protein Hydrolysate: Role of Novel Thermostable Keratinase From Bacillus pacificus RSA27 - Sharma, Chhavi; Timorshina, Svetlana; Osmolovskiy, Alexander; Misri, Jyoti; Singh, Rajni (Frontiers in Microbiology, 2022)
Microbial keratinases exhibit a momentous role in converting keratin biowastes into exceedingly valuable protein supplements. The present study reports a novel, highly stable keratinase from Bacillus pacificus RSA27 for the production of pure peptides rich in essential amino acids from chicken feathers. Purified keratinase showed specific activity of 38.73 U/mg, 2.58-fold purification and molecular weight of 36 kDa. Kinetic studies using chicken feather as substrate reports Km and Vmax value of 5.69 mg/mL and 142.40 µg/mL/min respectively, suggesting significant enzyme-substrate affinity/biocatalysis. Identification and in-silico structural-functional analysis of keratinase discovered the presence of distinct amino acid residues and their positions. Besides, keratinase possess high affinity calcium binding site (Asp128, Leu162, Asn164, Ile166 and Val168) and catalytic triad of Asp119, His151 and Ser308, known attributes of serine protease (subtilisin family). Further, scale-up to 5 L fermenter revealed complete feather hydrolysis (94.5%) within 24 h with high activity (789 U/mL) and total amino acid of 153.97 µmoles/mL. Finally, cytotoxicity evaluation of protein hydrolysate resulted in negligible cytotoxic effects (1.02%) on mammalian hepatoblastoma cell line, signifying its potential biotechnological applications.